A Phenomena of Emphasis in the Arabic Language: ظواهر التوكيد في اللغة العربية - Asmakin Antoro (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
This analytical rhetorical study explores the linguistic concept of Tawkid (Emphasis) in Arabic grammar and rhetoric. Tawkid is defined as a grammatical device that reinforces the meaning of the main word (the antecedent) and removes any potential misunderstanding or ambiguity arising from hesitation or error. The study identifies two primary types of Tawkid: verbal emphasis (al-tawkid al-lafzi) and semantic emphasis (al-tawkid al-ma‘nawi). Verbal emphasis occurs through the repetition of the original word—whether a verb, noun, particle, or sentence—to strengthen the intended meaning, while semantic emphasis reinforces the antecedent through words conveying a similar sense without repetition. In addition, this study discusses the purpose (ghard) of Tawkid in Arabic discourse, highlighting its rhetorical role in achieving clarity, precision, and expressive force.